Metode Penyusutan Mesin Produksi Dan Pengaruhnya Terhadap Biaya Overhead Pabrik - Wahyudin Hasan; Yopin Lamatenggo (Gorontalo Accounting Journal, 2018)
Fixed assets have a direct relationship with production processes such as machinery and factory buildings to generate future income for the company. This study aims to determine the shrinkage of the machine whether it is in accordance with accounting standards and to determine the effect of depreciation on the company's factory overhead costs which are measured using the method of working hours and methods of production.From the results of the study showed that PT Tri Jaya Tangguh still uses a straight-line method whose depreciation value is fixed every year and is not affected by the results / output produced while if using the working hours method and the method of production, the depreciation value will change every period and its depreciation will affect the company's factory overhead costs.